Lipoprotein-associated phospholipase A2 and risk of incident peripheral arterial disease in a multi-ethnic cohort: The Multi-Ethnic Study of Atherosclerosis. (February 2017) - Garg, Parveen K; Jorgensen, Neal W; McClelland, Robyn L; Jenny, Nancy S; Criqui, Michael H; Allison, Matthew A; Greenland, Philip; Rosenson, Robert S; Siscovick, David S; Cushman, Mary
Prospective studies supporting a relationship between elevated lipoprotein-associated phospholipase A2 (Lp-PLA2 ) and incident peripheral arterial disease (PAD) are limited. We evaluated the association of Lp-PLA2 with incident PAD in a multi-ethnic cohort without clinical cardiovascular disease. A total of 4622 participants with measurement of Lp-PLA2 mass and Lp-PLA2 activity and an ankle–brachial index (ABI) between 0.9 and 1.4 were followed for the development of PAD (median follow-up = 9.3 years), defined as an ABI ⩽0.9 and decline from baseline ⩾0.15. There were 158 incident PAD events during follow-up. In adjusted logistic regression models, each higher standard deviation of both Lp-PLA2 activity and mass did not confer an increased risk of developing PAD [odds ratios, (95% confidence intervals)]: 0.92 (0.66–1.27) for Lp-PLA2 activity and 1.06 (0.85–1.34) for mass. Additionally, no significant interaction was found according to ethnicity: p =0.43 for Lp-PLA2 activity and p =0.55 for Lp-PLA2 mass. We found no evidence of an association between Lp-PLA2 and incident PAD.